[INVITED] Cascade FBGs distributed sensors interrogation using microwave photonics filtering techniques. (March 2016) - Ricchiuti, Amelia L.; Hervás, Javier; Sales, Salvador
Abstract: Systems to interrogate photonic sensors based on long fiber Bragg gratings (FBGs) are illustrated and experimentally validated. The FBGs-based devices are used as quasi-distributed sensors and have demonstrated their ability to detect and measure the precise location of several spot events. The principle of operation is based on a technique used to analyze microwave photonics (MWP) filters. The overall idea beyond this work has been borne out and demonstrated step by step starting from preliminary test that have led to the development of a very-long distributed sensor based on an array of 500 equal and weak FBGs. Firstly, we have demonstrated the feasibility of the MWP filtering technique to interrogate a 10 cm-long high reflectivity (≈99%) FBG. Then, a pair of low-reflectivity (<6%) FBGs has been employed as sensing device. The latter has laid the foundation for the development and implementation of a 5 m-long fiber optic sensor based on 500 very weak FBGs. Spot events have been detected with a good spatial accuracy of less than 1 mm using a modulator and a photo-detector (PD) with a modest bandwidth of only 500 MHz. The simple proposed schemes result cost effective, intrinsically robust against environmental changes and easy to reconfigure. Highlights: FBGs-based distributed sensors able to measure the location of several spot events. Principle of operation based on a technique used for microwave photonics filters. Spatial accuracy of less than 1 mm using a modest bandwidth of only 500 MHz. Trade-off between the hot spot resolution and the system frequency bandwidth. Simple, cost effective, robust against environmental changes, easy to reconfigure.